Human Potential in Motion: An Empowerment Approach to Productive Growth in Correctional Institutions - Helena Gracelda Situmeang; Padmono Wibowo (Badan Strategi Kebijakan Hukum, 2025)
This study explores the empowerment strategies implemented at the Garut Class IIA Correctional Institution to activate inmates human potential, enhance productivity, and strengthen readiness for social reintegration. The research was conducted to address challenges such as low post-release employability, limited access to rehabilitation programs, and persistent social stigma toward former inmates. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation involving nine informants included two correctional officers, external partners (PT. CGI), and five inmates. Secondary data were drawn from official correctional reports, regulations, and previous studies. Data were analyzed using NVivo 12 software through coding, theme grouping, and data visualization to identify key patterns in empowerment strategies and outcomes. The findings indicate that empowerment programs at the Garut correctional facility effectively enhance inmates’ discipline, confidence, responsibility, and work skills. The program integrates two dimensions: personality development (religious, moral, and behavioral rehabilitation) and independence development (vocational training in livestock, agriculture, coconut fiber processing, sewing, and screen printing). Implementation of the Risk-Need-Responsivity (RNR) principle ensures that rehabilitation aligns with inmates’ risk levels, criminogenic needs, and learning responsiveness. Collaboration with PT Coir Global Indonesia strengthens the economic aspect of rehabilitation through sustainable production and fair incentives. The study concludes that empowerment through structured, participatory, and collaborative approaches effectively transforms inmates into productive and responsible individuals. However, challenges such as limited staff, facilities, and public stigma remain. Strengthening cross-sector collaboration and post-release support is essential to sustain empowerment and successful social reintegration.